The Discussion of Theory and Practice on Decentralization and Service Delivery - Mudalige, Priyantha W. (European Scientific Journal, ESJ, 2019)
In recent years, the responsibility of service delivery has strategically shifted from the central government to the most localised public sectors. Decentralization implies that a sub-national level government can choose between different measures and adapt service delivery to local circumstances or the characteristics of individual service recipients. Various governments around the world have started decentralization based on the principle of selfgovernance. It has many successes and has become a method of choice for people to get closer to goods and services. In addition, most governments have decided to use decentralization to empower the local population for political, economic, social, management, administration, and technology. As a result, local people can participate in the planning and management of development processes and decision-making. The specific objective of this paper is to discuss the relationship between decentralization and service delivery and is primarily based on literature review. Many governments have recognized the use of decentralization models based on their economic, political, cultural, and geographical factors, and decentralization could be understood as a process of expanding the role of sub-national governments. Every central government has to perform nationally-recognized functions. But sub-national level governments need to provide services and make decisions that are specific to their own affairs. Therefore, the decentralized structure plays a huge role in the administration and development of a country.